THE ROLE OF SOCIAL SUPPORT AND JOB STRESS AS PREDICTORS OF EMPLOYEE PERFORMANCE IN GEN Z - Puspa, Rani; Permana, Angrian (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
Human resources are the main and crucial element in achieving a company's goals. Effective management is very necessary to direct and move important factors in the organization, in order to achieve the goals that have been set. This research aims to determine the effect of Social Support and Work Stress on the performance of Zoomers generation employees in Serang City. The research method used was a quantitative approach with accidental sampling technique, involving 130 respondents who were employees of the Zoomers generation. Data analysis was carried out using SPSS version 25.0 software.The research results show that Social Support has a significant influence on employee performance, confirming the importance of support from colleagues, superiors, and the work environment in increasing productivity. In contrast, Job Stress does not show a significant influence on employee performance when tested individually. However, simultaneously, the Social Support and Job Stress variables together have a significant influence on employee performance. These findings provide important insights for companies in managing and empowering Zoomers generation employees, with a focus on increasing social support and managing stress in the workplace to improve overall performance